Penerapan Value Engineering pada Proyek Pembangunan Gedung - Sekur T Rematobi; Wennie Mandela; Ery Murniyasih (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
In the development of a construction project, cost control is very important in the process of managing project costs. Many problems will be encountered in a construction project such as wasteful use of materials, unskilled labor and late completion of the project. This causes waste of costs that do not match the specified budget. In the construction project of the Rectorate of the Sorong City Health Polytechnic building, a budget of Rp. 36,570,996,788.55 is required. This study aims to make savings on previously planned costs, in addition to knowing the comparison of total project costs after analysis. The method used in this study is the Value Engineering method. The Value Engineering method is a method used to identify and eliminate unnecessary activities or reduce costs without reducing function. There are 4 stages of the work plan in this method, namely: Information Stage, Creative Stage, Analysis Stage, and Recommendation Stage. After conducting the Value Engineering analysis, savings of Rp. 654,875,786.25 or 1.79% of the total project cost were obtained. The analysis was conducted on the two highest-cost work items: wall and floor work. For the wall work, it was recommended that the HPL wall covering be replaced with plasterboard, while for the floor work, it was recommended that the 60x60 granite be replaced with 60x60 ceramic tiles.